PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Kadek Adi Pratama Hendra; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2024)
A banking company is a company whose business activities are to receive cash and distribute it back in the form of credit in an effort to increase economic growth and equality and national economic stability which leads to increasing social welfare, this can reflect good company prospects in the eyes of investors. This research was conducted on banking companies listed on the Indonesia Stock Exchange in 2020-2022. This type of research is quantitative research. The sample in this research was obtained using a purposive sampling technique, namely selecting samples using predetermined criteria. Based on this technique, 45 samples were obtained from a total of 47 banking companies listed on the Indonesia Stock Exchange in 2020-2022. The data analysis technique used in this research is the multiple linear regression analysis method. Based on the results of the analysis, it shows that liquidity as proxied by the Current Ratio (CR) has no effect on company value. Solvency as proxied by the Debt to Equity Ratio (DER) has a negative and significant effect on company value. Profitability, which is proxied by Return On Assets (ROA), has a positive and significant effect on company value.